A Novel Level I Oncoplastic Surgery Technique for Tumors Located in UIQ of the Breast Far from the Nipple: The “Cross” Technique - Ahmad Kaviani, MD; Sanaz Zand, MD; Amir Ashraf-Ganjouei, MD; Rami Younan, MD; Remy Jacques Salmon, MD (Plastic and Reconstructive Surgery, Global Open, 2019)
Summary:. Breast surgery was revolutionized with the use of oncoplastic reshaping techniques minimizing breast deformities and esthetic complications. However, the application of the current oncoplastic techniques becomes challenging in some situations such as small-size breasts and when the tumors are located in special locations of the breast, for example, upper inner quadrant. In this article, an optimized oncoplastic technique named the “Cross” technique is introduced to overcome the abovementioned problems in the surgery of breast tumors located in the upper inner quadrant far from the center of the breast. Nineteen oncoplastic surgeries were performed by the same breast surgeon. The mean diameter and weight of the excised specimens were 20 mm and 74 g. The mean age of the patients was 51 years. Clear surgical margins were obtained in all patients. There was no marked deformity in the breast after surgery. The optimized technique produced promising results in our hands when applied to a selected group of patients. Moreover, the technique was found to reduce the need for revision surgery in ptotic breasts, as the alteration in the shape of the breast undergoing surgery is not significant enough to introduce asymmetry to the breasts.